2021
DOI: 10.1186/s40560-021-00539-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of noninvasive respiratory support with mortality and intubation rates in acute respiratory failure: a systematic review and network meta-analysis

Abstract: Background Noninvasive respiratory support devices may reduce the tracheal intubation rate compared with conventional oxygen therapy (COT). To date, few studies have compared high-flow nasal cannula (HFNC) use with noninvasive positive-pressure ventilation (NPPV). We conducted a network meta-analysis to compare the effectiveness of three respiratory support devices in patients with acute respiratory failure. Methods The Cochrane Central Register of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…High flow nasal cannula therapy may help avoid invasive mechanical ventilation in patients with hypoxemia (1). Recent studies have indicated that a high flow nasal cannula (HFNC) improves respiratory drive and lung mechanics and enhances CO 2 removal (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…High flow nasal cannula therapy may help avoid invasive mechanical ventilation in patients with hypoxemia (1). Recent studies have indicated that a high flow nasal cannula (HFNC) improves respiratory drive and lung mechanics and enhances CO 2 removal (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…However, its benefit in mortality is controversial. 8 , 9 In the setting of the current pandemic, HFO has been recommended over the use of non-invasive ventilation NIV 10 , 11 , despite limited evidence regarding its benefit in improving outcomes. Nonetheless, with a global shortage of mechanical ventilators and access to specialized care, HFO may be a useful alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Learners develop skills through supervised deliberate practice and the provision of feedback. 2,3 Due to a variety of factors, such as the introduction of new technology and changes in standards of care, 4,5 there has been a decrease in the overall number of procedures being performed, particularly some of the higher risk procedures, such as cricothyrotomy, pericardiocentesis, and lumbar puncture. 6 These high-acuity, low-opportunity procedures are increasingly taught via simulation given the lack of exposure in the clinical environment.…”
Section: Introductionmentioning
confidence: 99%